Role of a novel cationic gemini surfactant (CGS) on a one-step sol–gel process and photocatalytic properties of TiO2 powders - Melek Koç Keşir; İkbal Sarıkaya Yıldız; Selçuk Bilgen; Münevver Sökmen (Journal of Water and Health, 2022)
TiO2 nanoparticles were prepared using a sol–gel process in combination with a novel cationic gemini surfactant (CGS) with amide functional groups at low temperatures. Titanium (IV) isopropoxide (TIP) and CGS were used as the starting materials and as effective agents, respectively, to orient the nanoparticles during the sol–gel synthesis. To reveal both the structural and morphological properties of the nanopowders prepared in this work, they were characterized using X-ray diffraction (XRD) analysis, scanning electron microscope (SEM), and Brunauer–Emmett–Teller (BET) surface area apparatus. The pore volume and pore size were calculated using the Barrett–Joyner–Halenda (BJH) model on the desorption branch. The experimental results show that the surface area and average crystallite size of the obtained TiO2 nanopowders vary between 160–203 m2/g and 27–49 nm, respectively. It was observed that the N2 adsorption–desorption isotherms for almost all samples of TiO2–X% CGS (X: mass of CGS) show the typical Type I with a hysteresis loop of H4. The photocatalytic activities of the CGS-modified nanocomposites are evaluated not only by the photocatalytic degradation of methyl orange (MO) but also by the reduction of Cr(VI) as model pollutants in the presence of visible light. HIGHLIGHTS Excitable TiO2/CGS composites were prepared by the sol-gel method.; XRD, SEM, BET, and N2 adsorption-desorption measurements were done for structural properties.; Photocatalytic activity of TiO2/CGS nanocomposite was evaluated on both the photoreduction of Cr(VI) ions and photooxidation of methyl orange under irradiation from a 365 nm lamp.; Utilized in this survey is a cationic gemini surfactant that has a similar CTAB structure and has two long chains and cationic head groups and is a preferred morphology agents. Compared to one head group with CTAB, a novel synthesized cationic surfactant with two long chains is anticipated to positively affect both the properties of catalyst structures and data of photocatalytic degradation of model pollutants.;